Estudo das características hidroclimatológicas no município de Janaúba e método de estimativa de contribuição da precipitação na barragem do Município - Pinho, Vinicius Nunes (2014)
Janaúba is a city located in northern Minas Gerais state, Brazil. With an area of 2,188.842 km ², the city is bathed by Gorutuba River, which divides the municipalities of Nova Porteirinha and the Riacho dos Machados. Its main activities are agriculture and services (trade). It is the 2nd largest city in Northern Minas and 52 statewide. The overall objective of the study is the weather in the region of Janaúba, analyze the behavior of rain during the period, classify the type of climate in the county and assess the water conditions of the municipality. Also prepare a functional method to estimate the volumes of precipitation and its contribution within the dam that supplies the municipality. To analyze the pattern of rainfall, each region proceeds in order interference of static and dynamic nature factors. The use of probability functions is directly linked to the nature of the data relate. From this, criteria for discriminating the relation of each period were prepared. Dry period is one in which the total rainfall accumulated in the four wettest consecutive months is equal to or less than the amount corresponding to 25% probability and rainy period: one whose total precipitation, accumulated in the four wettest consecutive months, is higher than that corresponding to the 75% probability value. Were used for this study historical series of 17 rain gauges extracted HIDROWEB system of the National Water Agency (ANA) and the National Institute of Meteorology (INMET). The posts that had been passed through a failure system, failures and filling consistency analysis, to be rendered valid for the assessment of the precipitation region. The average rainfall in the municipality of Janaúba, presents two well-defined periods, a dry and a wet season. The dry season is between the months from April to October and the rainy season between November and March, largely influenced by the performance of the ZCAS. The climate in the region is semi-arid with high temperatures and mean annual precipitation of 766 mm. The soil of the county has great water deficit most of the year except the rainy season, when it has a surplus. The municipality of Janaúba, has a dam which is responsible for water supply throughout the county. The annual rainfall can maintain the level of the dam in years with rainfall within or above the normal range. The rain that falls in the region of contribution of the dam, has a yield of 10.18% and it is possible to estimate the contribution of rainfall in the influent volume of the dam. A rain of 100 mm within the catchment area of the dam, contributes with 15.57% of the influent annual volume, and the mirror is 2,81 m Water increase. If we take into account the total rainfall of the rainy period to one year within the average range, the contribution is 99.21%, supplying the water demand of the city.